PENGGUNAAN KATALIS MgF2 DALAM SINTESIS SENYAWA TURUNAN AMOKSISILIN - Hadi Barru Hakam Fajar Siddiq (JURNAL ILMIAH FARMASI AKADEMI FARMASI JEMBER, 2021)
The synthesis of amoxicillin derivatives was carried out by reaction of amoxicillin with p-aminophenol which was catalyzed by MgF2. The aims of this research was to characterize amoxicillin derivatives. The compounds have been characterized by physical and chemical tests including organoleptic test, melting point test, pH test, Rf value test and maximum wavelength test. The results showed that the compounds having physical characteristics including organoleptic was brown powder and bitter taste with 238°C melting point. The chemical characteristic showed that Rf value was about 0.6, a pH was 6,1 and a maximum wavelength was 311 nm.